MENGATASI KECEMASAN SISWA MENGHADAPI PEMBELAJARAN DARING MELALUI KONSELING RATIONAL EMOTIVE THERAPY DENGAN TEKNIK DESENSITISASI SISTEMATIS - Fitri Nur Aini; Masturi Masturi; Nur Mahardika (Universitas Muria Kudus, 2022)
This study aims to: (1) describe the factors that influence students' anxiety in facing online learning in students at SMPN 2 Gebog Kudus (2) Overcoming students' anxiety facing online learning through Rational Emotive Therapy counseling with systematic desensitization techniques at SMPN 2 Gebog Kudus. The subjects studied were 2 class VIII students of SMP N 2 Gebog Kudus who experienced anxiety in facing online learning. The method of data collection uses the method of observation, interviews, and documentation which is carried out in depth so that later it will get accurate results on the problems studied by the author. Based on the results of the study, it can be concluded that counselees experience anxiety in facing online learning which is characterized by not understanding the material, fear of online assignments, lack of concentration in learning, experiencing obstacles in learning, and fear of not going to class. To assist counselees in overcoming anxiety in facing online learning, rational emotive therapy counseling is given with systematic desensitization techniques. By using rational emotive therapy counseling, systematic desensitization techniques can produce behavioral changes in clients to be able to understand the material, not afraid of assignments, able to concentrate on learning, have no learning barriers, and believe that they can go to class.